Intraspecific and interspecific olfactory interactions and density of leopards Panthera pardus (Linnaeus, 1758) in Sabi Sands Game Reserve, South Africa - Somers, Michael J. (University of Pretoria, 2022)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2021.